Applications of the Glycine Nitrate Combustion Method for Powder Synthesis on the LSGM-based Electrolyte-Supported Solid Oxide Fuel Cells. (30th May 2017) - Chen, Yu-Ming; Lin, Tai-Nan; Liao, Ming-Wei; Kuo, Hong-Yi; Yeh, Chun-Yen; Kao, Wei-Xin; Yang, Sheng-Fu; Wu, Kuan-Ting; Ishihara, Tatsumi
Abstract : Solid oxide fuel cells (SOFCs) are recognized as environmentally friendly, highly efficient devices, and alternatives to conventional energy conversion systems. Typical material design used is the YSZ-based cell consisted of NiO-YSZ and LSM as anode and cathode, with a dense electrolyte of YSZ. When considering the use of hydrocarbon fuels, carbon deposition has been observed as major failure issue in electrodes. Also the homogeneity of the electrolyte is essential for the gas-tightness after sintering process. In this article, we propose an innovative chemical reactor with powder collection system and its application to glycine-nitrate combustion process to produce precision ceramic powder in nano scale, not only generates precision ceramic powder of specific chemical composition in a mass-production scale, but also the system has the primary features of withstanding the instant high-temperature flare and pressure during powder formation reaction. Electrodes/electrolyte powders, SmBa0.5 Sr0.5 Co2 O5+δ (SBSC), Ce0.6 Mn0.3 Fe0.1 O2 (CMF), and La0.9 Sr0.1 Ga0.8 Mg0.2 O3- d (LSGM), have been synthesized and characterized for the crystallinity, microstructure, conductivity, coefficient of thermal expansion properties were studied. The material application to form an SOFC has been executed and cell performances are investigated as well.